Association Between Injection and Microseismicity in Geothermal Fields With Multiple Wells: Data-Driven Modeling of Rotokawa, New Zealand, and Husmuli, Iceland - Yu, Pengliang; Dempsey, David; Rinaldi, Antonio Pio; id_orcid:0 000-0001-7052-8618; Calibugan, Aimee; Ritz, Vanille; id_orcid:0 000-0002-8773-7608; Archer, Rosalind (American Geophysical Union, 2023)
Understanding injection-induced microseismicity in geothermal systems can provide insight into reservoir connectedness. However, fault and reservoir complexity are difficult to represent in simple analytical models, which makes it difficult to discern clear relationships from incidental associations. Here, we have used data-driven models to study how fluid injection and microseismicity are related in the Rotokawa (New Zealand) and Hellisheioi (Iceland) geothermal fields. We tested two classes of model: (a) lagged linear regression of seismicity rate as a function of well injection rates; and (b) systematic extraction of injection time series features that are then evaluated for associations with the seismicity. These models allowed us to determine which wells had the greatest correlation with microseismicity and to explain this association in a reservoir context. Finally, exploring different data types and transformations, we were unable to establish a link between rapid changes in injection rate and seismicity spikes, as suggested by some theoretical models. ISSN:2169-9313 ISSN:0148-0227 ISSN:2169-9356